Reduced White Matter Integrity With Cognitive Impairments in End Stage Renal Disease - Yin, Yi; Li, Meng; Li, Chao; Ma, Xiaofen; Yan, Jianhao; Wang, Tianyue; Fu, Shishun; Hua, Kelei; Wu, Yunfan; Zhan, Wenfeng; Jiang, Guihua (Frontiers in Psychiatry, 2018)
Background: End-stage renal disease (ESRD) is a serious public health problem, which can often lead to multiorgan dysfunction, such as cerebrovascular disease and cognitive damage. It is essential to understand cognitive impairment in patients with ESRD to develop better ESRD treatment and prevent further cognitive impairment. Cognitive impairment is believed to be related to structural abnormalities in the brain. Purpose: To investigate white matter microstructural abnormalities in patients with ESRD using TBSS analysis of DTI and to explore the possible mechanisms underlying the impaired cognitive function. Materials and Methods: A TBSS analysis of DTI data was to investigate the microstructural changes in their WM over the whole brain. We chose the white matter tracts or regions with significantly reduced FA as the regions of interest (ROIs), Pearson’s correlations were performed between clinical indicators (Mini-Mental State Examination (MMSE), digit span task scores, serum creatinine, blood urea nitrogen and hemodialysis duration) and the mean FA value of the regions of interest (ROIs) in the ESRD patients. Results: lower FA and higher MD, AD and RD values were observed in widespread and symmetrical WM in ESRD patients than healthy controls (HCs), Pearson correlation analysis revealed a significantly positive correlation between the Mini-Mental State Examination (MMSE) scores and FA values in the right corona radiata and left anterior thalamic radiation and demonstrated a significantly negative correlation between FA values and the serum creatinine and blood urea nitrogen in the anterior thalamic radiation (P<0.01). in addition, digit span task scores positively correlate with the FA value in the left anterior rather than in the corona.No cluster survived when we adopted the False Discovery Rate (FDR) correction to multiple comparisons. Conclusion: our study indicate widespread impairment of the white matter in ESRD patients. Damage to the thalamic radiation and corona radiata may affect cognitive function in ESRD patients, The reduced integrity of anterior thalamic radiation may tend to affect the working memory while the damage to the corona radiata may involve the excutive function impaired in ESRD patients. The accumulation of serum creatinine and blood urea nitrogen may contribute to the WM impairment.